Intense broadband 3.1 μm emission in Er3+-doped fluoroaluminate-tellurite glass for mid-infrared laser application. Issue 20 (15th October 2022) - Zhang, Chuncheng; Zhang, Chaomin; Yun, Chao; Lai, Shengying
Abstract: Er 3+ single doped fluoroaluminate-tellurite glasses were made by employing a conventional melt-quenching technique. A strong fluorescence around 3.1 μm was achieved from Er 3+ -doped fluoride glasses, under a 980 nm laser diode pump, which was assigned to the Er 3+ : 4 S3/2  →  4 F9/2 radiation transition process. The up-conversion and mid-infrared spectra of emission for fluoroaluminate-tellurite glasses with various concentrations of Er 3+ ions dopant was researched. In addition, the calculated fluorescence lifetime value about 3.1 μm reaches 0.48 ms. The findings indicate that fluoroaluminate-tellurite glasses doped with Er 3+ have prospects of being developed into 3.1 μm mid-infrared fiber and laser materials.